PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN DI ERA DIGITAL: REFLEKSI MAHASISWA - Acep Acep; Abdurahman Abdurahman (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2026)
ABSTRACT Civic Education plays a crucial role in shaping responsible and well-characterized citizens in the digital era, marked by rapid information flow and challenges in digital literacy. However, studies examining students’ perceptions of its implementation in higher education remain limited. This study aims to analyze students’ perceptions of the implementation of Civic Education at Universitas Indraprasta PGRI, focusing on learning problems, material relevance, instructional methods, and effectiveness in the context of digital citizenship. The novelty of this study lies in emphasizing the relationship between participatory pedagogical strategies and the strengthening of students’ digital citizenship character. This research employed a qualitative case study approach using structured interviews, observations, and documentation involving students from three study programs. Data were analyzed through data reduction, data display, and conclusion drawing with source triangulation to ensure validity. The findings reveal tendencies toward individualism, rule violations, and suboptimal digital media ethics. Materials on state defense, human rights, and democracy were perceived as relevant when linked to digital issues, while opinion-based discussions and cooperative learning were considered more effective. The main conclusion confirms that the effectiveness of Civic Education in the digital era depends on integrating civic values with contextual, participatory, and technology-adaptive learning strategies. ABSTRAK Pendidikan Kewarganegaraan berperan penting dalam membentuk warga negara yang berkarakter dan bertanggung jawab di era digital yang ditandai percepatan arus informasi dan tantangan literasi digital. Namun, kajian mengenai persepsi mahasiswa terhadap implementasinya di perguruan tinggi masih terbatas. Penelitian ini bertujuan menganalisis persepsi mahasiswa terhadap pelaksanaan pembelajaran Pendidikan Kewarganegaraan di Universitas Indraprasta PGRI, meliputi permasalahan pembelajaran, relevansi materi, metode, dan efektivitasnya dalam konteks kewargaan digital. Kebaruan penelitian ini terletak pada penegasan hubungan antara strategi pedagogis partisipatif dan penguatan karakter kewargaan digital mahasiswa. Penelitian menggunakan pendekatan kualitatif studi kasus dengan teknik wawancara terstruktur, observasi, dan dokumentasi terhadap mahasiswa dari tiga program studi, yang dianalisis melalui reduksi, penyajian, dan penarikan kesimpulan dengan triangulasi sumber. Hasil menunjukkan adanya kecenderungan individualisme, pelanggaran tata tertib, serta belum optimalnya etika bermedia digital. Materi bela negara, hak asasi manusia, dan demokrasi dinilai relevan jika dikaitkan dengan isu digital, sementara metode diskusi opini dan pembelajaran kooperatif dipersepsikan lebih efektif. Simpulan utama menegaskan bahwa efektivitas Pendidikan Kewarganegaraan di era digital bergantung pada integrasi nilai kewargaan dengan strategi pembelajaran yang kontekstual, partisipatif, dan adaptif terhadap perkembangan teknologi.